Drinking and Alcohol-Related Problems Among Minority Women - Caetano, Raul (Alcohol Health Res World, 1994)
Although drinking by black and Hispanic women in the United States differs from that of white women in terms of prevalence rates and incidence of alcohol-related problems, factors such as age and employment status have similar effects on drinking in each group. However, influences on drinking among minority women are complex and must be thought of as an interaction of cultural, personal, and historical factors. This interplay is beginning to emerge from ethnic studies.